(untitled) (Sustainability in Debate, 2016)
The main objective of the present text is to analyze environmental governance in the Sustainable Development Reserve Igapó-Açu, located in the municipalities of Manicoré, Borba and Beruri, state of Amazonas, Brazil. The study area was chosen because the RDS is the only Amazonas state protected area crossed by a federal interstate highway. This highway provides a specific territorial arrangement of governance elements in the studied area. Different methodological tools were used in this research, such as close-ended questionnaires and open-ended interviews. Data were systematized using Excel software and they were graphically represented in the form of organizational charts drawn with Websphere Analysis Software. Results indicate that environmental governance of the RDS Igapó-Açu involves multiple factors, while the central node of the local political articulation is held by a Management Council that is in charge of materializing the governability of the RDSt, as well as its ramifications.